Artificial Intelligence as an Enabler of Differentiated Arabic Language Instruction in Inclusive Secondary Education - Hadi, Nurul; Bukhory, Umar (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
Differentiated instruction is essential for inclusive education, yet its implementation in Arabic language learning remains challenging. This study examines the implementation of differentiated instruction in inclusive Arabic language classrooms and explores the role of Artificial Intelligence (AI) in supporting its implementation. A qualitative field research design was employed at four public Islamic senior high schools in Madura, Indonesia. Data were collected through classroom observations, in-depth interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman, and SaldaÃ±a. The findings indicate that differentiated instruction remains concentrated on learning products, while differentiation of content and instructional processes is still limited. AI assists teachers in simplifying learning materials, developing instructional media, providing adaptive learning activities, and designing flexible assessments that accommodate diverse learning needs. These findings demonstrate that AI functions as a pedagogical enabler that strengthens differentiated instruction, making Arabic language learning more inclusive, adaptive, and learner-centered.